Doping effects of fluorinated chiral dopant in blue phase liquid crystals and its electro-optical behavior. Issue 2 (26th January 2020) - Gao, Liang; Ma, Hongmei; Sun, Yubao
ABSTRACT: We reported a fluorine-containing binaphthyl derivative, denoted as BD-F, which showed a low helical twisted power. The blue phase liquid crystal (BPLC) doped with BD-F achieved a lower operating voltage than that only used traditional chiral dopant, resulting from the larger dielectric property of fluorinated BD-F. In addition, the BPLC composite exhibited a wider temperature range and an enhanced Kerr effect with the decreased frequency. In terms of the applications, the devices revealed microsecond response time, thereby providing broad prospects for photonics and displays. Graphical abstract: uf0001